KESEJAHTERAAN PSIKOLOGIS TAHANAN DITINJAU DARI DUKUNGAN SOSIAL KELUARGA - Ilham Maaruf; I Rheny Arum Permitasari (IMAGE, 2023)
This research aims to determine the relationship between family social support and the psychological well-being of prisoners at the Dittahti Regional Police Detention Center Java. The sample used was 85 prison inmates. The sampling technique used was purposive sampling. The analysis used is the non-parametric Spearman-rho correlation test. The psychological well-being variable is measured using a Likert scale based on Ryff's theory. Variable aspects of psychological well-being include self-acceptance, positive relationships with others, autonomy, environmental mastery, purpose in life dan personal growth. The social support variable was measured using a Likert scale based on Sarafini and Smith's theory with aspects of emotional or esteem support, tangible or instrumental, informative support, and companionship support. Based on the research results, a coefficient of 0.912 was obtained with a significance level of 0.00 or meaning p < 0.01. This means that there is a positive relationship between family social support and psychological well-being in prisoners at the Dittahti Regional Police of Central Java detention center. The family social support variable has an effective contribution of 83.8% to the respondent's psychological well-being variable. The level of psychological well-being of 56.5% of respondents was classified as high, while 43.5% of respondents were classified as moderate. Keywords : Performance, Integrity, Organizational Commitment